Pulses as a candidate crops for doubling farmers’ income - Singh, N. P. (Indian Farming, 2018)
In presence of newer and continuous challenges such as growing population with high demand for protein, shrinking agricultural land, unfavorable climate change coupled with increasing incidence of biotic and abiotic stresses, pulses as a candidate crop could contribute immensely towards doubling farmers income through effective efforts oriented towards diminishing cost of production through efficient technological options, site specific management of agro-inputs, quality assurances of these and employing resource saving measures. Enhancing income of farmers with scaling productivity through sound technological backups, quality seed/input availability. Possible horizontal expansion in pulses through acquiring new niches (rice fallows and others), cropping system intensification (inter-/mixed-and rotation) and utera cultivation can also significantly enhance the income level of farmers of targeted area. Reducing the cost of cultivation, scaling per unit productivity, efficient marketing networks and successful technology delivery mechanisms with due emphasis on sustainable intensification and crop diversification, climate resilient production technologies backed with strong research outputs in pulses that can contribute immensely towards doubling the farmers income.